Participatory Budgeting in Chile and its Contribution to Social Inclusion - Noriega Soto, Andrés Iván (2016)
This paper proposes to compare the profile of participants and non-participants of Participatory Budgeting (PP by its Spanish acronym) in Chile with the objective to provide empirical evidence about whether if it constitutes as a mechanism that contributes to social inclusion, particularly to those groups that traditionally have been excluded from democratic spaces at a local level. Three communes from the southern part of the country that are currently using this process were used as case studies: Lautaro, Río Negro y Puerto Montt. The main result of this study is that, in practice, the PP has not managed to fully include citizens, noticing in the results that young people, without organizational power, are the least favored in terms of participation. The dimensions considered were age, territorial and organizational, through a quantitative methodology and document analysis techniques.